О разработке технологии механохимической и термической деструкции биомассы в жидкие и газообразные топлива - Кузин, А. К.; Пличко, В. С. (НТУ "ХПИ", 2006)
Proposals on development of technology for mechanical/chemical and thermal destruction of biomass into fluid and gas fuels in presence of catalysts and activating agents are given. In laboratory conditions, the fluidization of wood dust, excessive active sludge from waste water treatment plants by biological method and hydrolytic lignin has been carried out
Keywords: твердые бытовые отходы; термическая деполимеризация отходов; отходы бытовые; пиролиз; утилизация отходов; топливо